2019
DOI: 10.1038/s41593-019-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Working memory revived in older adults by synchronizing rhythmic brain circuits

Abstract: Understanding normal brain aging and developing methods to maintain or improve cognition in older adults are major goals of fundamental and translational neuroscience. Here, we show a core feature of cognitive decline - working memory deficits - emerges from disconnected local and long-range circuits instantiated by theta-gamma phase-amplitude codes in temporal cortex and theta phase synchronization across frontotemporal cortex. We developed a noninvasive stimulation procedure for modulating long-range theta i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
420
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 486 publications
(445 citation statements)
references
References 101 publications
19
420
1
5
Order By: Relevance
“…[30][31][32] The study found that tACS enhanced TGC and working memory, and there was an association between changes in TGC and changes in working memory. 29 Moreover, this physiologically informed tACS restored TGC and working memory in older adults to the levels of younger adults compared with sham tACS. 29 TGC depends on the integrity and robustness of local and longrange neural circuits 33 and can serve as a biological target for NIBS interventions.…”
Section: Transcranial Magnetic and Electrical Stimulation In Alzheimementioning
confidence: 84%
See 3 more Smart Citations
“…[30][31][32] The study found that tACS enhanced TGC and working memory, and there was an association between changes in TGC and changes in working memory. 29 Moreover, this physiologically informed tACS restored TGC and working memory in older adults to the levels of younger adults compared with sham tACS. 29 TGC depends on the integrity and robustness of local and longrange neural circuits 33 and can serve as a biological target for NIBS interventions.…”
Section: Transcranial Magnetic and Electrical Stimulation In Alzheimementioning
confidence: 84%
“…29 Moreover, this physiologically informed tACS restored TGC and working memory in older adults to the levels of younger adults compared with sham tACS. 29 TGC depends on the integrity and robustness of local and longrange neural circuits 33 and can serve as a biological target for NIBS interventions. Patients with AD experience significant impairment in working memory and TGC during working memory performance; however, patients with MCI experience impairment in only TGC, 34 suggesting that TGC could serve as a target for early interventions that would aim at prevention of cognitive decline.…”
Section: Transcranial Magnetic and Electrical Stimulation In Alzheimementioning
confidence: 84%
See 2 more Smart Citations
“…In the past decades, clinicians and researchers are able to use some well‐established brain stimulation techniques, such as electroconvulsive therapy (ECT), deep brain stimulation (DBS), or transcranial magnetic stimulation (TMS) for treating neurological and psychiatric disorders. Other technologies, like transcranial random noise stimulation (tRNS), transcranial direct/alternating current stimulation (tDCS/tACS), transcranial focused ultrasound stimulation (tFUS), and vagus nerve stimulation (VNS) are mainly employed as experimental tools in cognitive and clinical neuroscience, with some successful therapeutic applications in clinical trials . In addition, novel stimulation methods, such as high‐definition transcranial direct current stimulation (HD‐tDCS), combining imaging brain stimulation, and closed‐loop brain stimulation, are the emerging and existing stimulation techniques, which need to be refined in the future studies.…”
mentioning
confidence: 99%